Pijat Bayi sebagai Cara Menaikkan Berat Badan Bayi Usia 3 – 6 Bulan - Mawaddah, Sofia; Mursyidah, Mursyidah (Jurnal Kebidanan Malakbi, 2021)
Massage has been used for medicinal purposes and has been a routine part of infant care for hundreds of years in many cultures and is one of the oldest therapeutic techniques in the world. Massage has become a component of the development of supportive care. Infant massage as a form of alternative medicine is becoming increasingly popular because of its simplicity, cost effectiveness, easy learning and can be done at home by families. Data from the Baamang II Health Center in 2017, there were 4,738 babies who weighed, the results obtained 277 babies who did not gain weight. The aim is to determine the effect of infant massage on body weight of infants aged 3 – 6 months. The method used in this research is quantitative research, quasi-experimental design with one group pretest posttest design, namely research activities that provide a pretest before being given treatment, after being given treatment then giving a final test (posttest) with a population of 98 babies weighing in the Baamang II Public Health Center in February – May 2019. The number of samples in this study were 32 infants aged 3 – 6 months at Baamang II Public Health Center. The result of the Paired T-Test statistical test shows a P-Value of 0.000 (P-Value < α 0.05) so that it can be concluded that there is an effect of infant massage on body weight of infants aged 3 – 6 months in the Baamang II Public Health Center. The conclusion is that there is an effect of the effect of infant massage on body weight of infants aged 3 – 6 months in the Baamang II Public Health Center.